ANALISIS PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) SEBELUM DAN SESUDAH DIBERLAKUKANNYA UU PPH NO. 36 TAHUN 2008 - Marentek, Jessica Fergie; Elim, Inggriani; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
In order to deal with the impact of the global financial crisis, the government lowered the tax rates at the rate of 28% starting in 2009 and will be 25 % starting in 2010. It aims to support the state revenues from taxation so it become more stable. Ratio of profitability that researchers used in this study is Gross Profit Margin, Operating Profit Margin, Return On Investment, and Return On Equity. Researchers conducted the study using descriptive statistical analysis methods with data taken from Indonesia Stock Exchange (IDX), and processed using SPSS v.20 compare means-paired samples T-test program. The samples are 60 manufacturing companies in 2009 and 2010. The results showed that there was no significant difference between the GPM in 2009 and 2010 with a value of thitung < ttable (1.729 < 2.045) at Î± = 0.05 . The results also showed that there was no significant difference between the OPM in 2009 and 2010 with a value of thitung < ttable (0.230 < 2.045) at Î± = 0.05. The results also showed that there was no significant difference between the ROI in 2009 and 2010 with a value of thitung < ttable (0.044 < 2.045) at Î± = 0.05. And the results of the study also showed that there was no significant difference between the ROE in 2009 and 2010 with a value of thitung < ttable (0.417 < 2.045) at Î± = 0.05 .